2023
DOI: 10.3390/geosciences13070189
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Prediction of Longitudinal Settlement of Existing Tunnel Using ConvRes-DLinear Model with Integration of Undercrossing Construction Process Information

Abstract: Undercrossing construction can cause severe structural deformation of the above existing tunnel in operation. The induced longitudinal differential settlement between the segments can pose a huge risk to running subways, hence it is of great importance to monitor and predict the settlement. Within this study, a Wireless Sensor Network (WSN) system was implemented to obtain hourly monitoring data of settlement from the very beginning of undercrossing to post construction period. An improved direct multi-step (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Increase in face pressure force [15,[17][18][19] Although the influences of these operation parameters are identified, the quantitative measurements of these operation parameters on jacking forces remain absent. Recent research has shown the use of machine learning and deep learning techniques in the pipe jacking process, such as predicting the changes in geological conditions [26][27][28][29], changes in ground settlement [30][31][32][33][34][35] and prediction of various operation parameters [36][37][38][39][40]. Hence, this paper will use deep learning techniques, such as gated recurrent units (GRUs) with an attention mechanism, to predict jacking forces through a region of weathered phyllite based on pipe jacking operation parameters as the input features.…”
Section: Jacking Speedmentioning
confidence: 99%
“…Increase in face pressure force [15,[17][18][19] Although the influences of these operation parameters are identified, the quantitative measurements of these operation parameters on jacking forces remain absent. Recent research has shown the use of machine learning and deep learning techniques in the pipe jacking process, such as predicting the changes in geological conditions [26][27][28][29], changes in ground settlement [30][31][32][33][34][35] and prediction of various operation parameters [36][37][38][39][40]. Hence, this paper will use deep learning techniques, such as gated recurrent units (GRUs) with an attention mechanism, to predict jacking forces through a region of weathered phyllite based on pipe jacking operation parameters as the input features.…”
Section: Jacking Speedmentioning
confidence: 99%